Synthesis and Estimation of the Insecticide and Antibacterial Activities for Some New Amide Derivatives - Zinah Hussein Ali; Dina Saleem; Abbas Khudhair Abbas; Baneen Salam Rasool; Mustafa Sabri Cheyad (Indonesian Journal of Chemistry, 2023)
In this work, new compounds of amide derivatives (C1-C3) were synthesized through the conversion reaction of p-chloroaniline to diazonium salt (B1), which reacts with aniline to form a new azo-compound (B3). Synthesized of p-alkoxybenzoic acid (A1-A3) and reacts with SOCl2 to form A4-A6 compounds that react with B3 compound to form amide compounds (C1-C3). The synthesized derivatives were tested by docking analysis and characterized via FTIR, 1H-NMR spectra. In the docking study, the interaction diagram also displays many van der Waals interactions, which are used to estimate the synthetic compounds' activity as insecticides like anti-termites. Heptyl came in first on the binding score, followed by octyl and then nonyl. Due to the compounds' modified conformation in interacting with the enzyme's binding pocket, the length of the alkyl residue of the derivative adversely impacted their binding inhibition. The synthesized compounds (C1 and C3) give a good result as anti-E. coli and anti-Staphylococcus strains.